Mindfulness in Learning: An Effect of Mindful Breathing Practice on the Learning Concentration of Students - Dharma Nata Saputra; Burmansah Burmansah; Eko Pramono; Susanto Susanto; Rina Manggalani; Ria Astika; Tejo Ismoyo (Universitas Sebelas Maret, 2024)
Mindful Breathing practice on the concentration of high school students' learning in 2024. The problems that occur in students are that there are still students who are busy and like to daydream, are less interested, and feel bored. In addition, feeling stiff, sleepy, crowded class conditions, and less favorite materials can also make it boring and difficult to concentrate, and hunger and gadgets (cell phones) can also interfere with their concentration in learning. Proportional Random Sampling technique. The study was conducted at a Senior High School with respondents from the school's students in the 2024/2025 academic year. The results of the study showed that there was a significant favorable influence between the practice of Mindful Breathing on Students' Learning Concentration with t_hitunga value of 5.212 and a significance value (p) of 0.000 <0.05. From the results of the simple regression analysis calculation, the R square determination value was found to be 0.190, which means that the practice of mindful breathing has a 19% effect on students' learning concentration, while other factors influence the remaining 81%.